Learn in conversation. An exercise to recover popular knowledge made in the province of Santa Fe (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
This article describes and analyzes the extension work made by a team of researchers and teachers in order to of produce a specific recipe book for the province of Santa Fe. The article begins by marking the value of recipes and food in culture with the purpose of arguing the meaning of the proposal. Then it continues with the proposal of the methodological decisions that led to the work carried out. Finally, the results obtained are detailed. This proposal allowed the publication of a collective recipe book that accounts for the food actually consumed in the province, but also for the characteristics, disputes, and tensions of knowledge production work in the territory.
Keywords: cooking recipes; extension; memory; Santa Fe; recipe book